Effect of Chemical Solvents on the Wetting Behavior Over Time of Femtosecond Laser Structured Ti6Al4V Surfaces - Georg Schnell; Christian Polley; Stephan Bartling; Hermann Seitz (Nanomaterials, 2020)
The effect of chemical solvents on the wetting state of laser-structured surfaces over time is systematically examined in this paper. By using a 300-fs laser, nanostructures were generated on Ti6Al4V, subsequently cleaned in an ultrasonic bath with different solvents and stored in ambient air. The static contact angle showed significant differences for cleaning with various solvents, which, depending on the applied cleaning and time, amounted up to 100°. X-ray photoelectron spectroscopy analyses reveal that the cleaning of the laser-structured surfaces affects the surface chemistry and the aging behavior of the surfaces, even with highly volatile solvents. The effect of the chemical surface modification is particularly noticeable when using alcohols for cleaning, which, due to their OH groups, cause highly hydrophilic behavior of the surface after one day of storage. Over the course of 14 days, enrichment with organic groups from the atmosphere occurs on the surface, which leads to poorer wetting on almost every structured surface. In contrast, the cleaning in hexane leads to a fast saturation of the surface with long-chain carbon groups and thus to a time-independent hydrophobic behavior.